If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 0.10x = 0.15x + 8 Reorder the terms: 6 + 0.10x = 8 + 0.15x Solving 6 + 0.10x = 8 + 0.15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.15x' to each side of the equation. 6 + 0.10x + -0.15x = 8 + 0.15x + -0.15x Combine like terms: 0.10x + -0.15x = -0.05x 6 + -0.05x = 8 + 0.15x + -0.15x Combine like terms: 0.15x + -0.15x = 0.00 6 + -0.05x = 8 + 0.00 6 + -0.05x = 8 Add '-6' to each side of the equation. 6 + -6 + -0.05x = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -0.05x = 8 + -6 -0.05x = 8 + -6 Combine like terms: 8 + -6 = 2 -0.05x = 2 Divide each side by '-0.05'. x = -40 Simplifying x = -40
| -7x+7(-3x+18)=-14 | | 15h-11h=20 | | 1.25n=4 | | -5/6+x=11/6 | | -5=(x+9) | | 12x+14+10v=80 | | 36/x-8=6/7 | | 5x-9=-3x-25 | | x/5-13=22 | | y=7/8(0)+5y | | 6x+2(6x-3)=-144 | | 2x-2x/7=x/2+17/2 | | 16x+1=-14 | | 2(x+10)=x-7 | | -5(w+5)= | | -6x-76=98-12x | | -1+6x=3x-19 | | (27p^6)^(5/3) | | -6-k+2-5k= | | 8x-2(x-8)=6(x+1)+7 | | 5-10t=-25 | | 40=5x+2(-x+2) | | x^2-23x=3 | | -2y+9-y=-7y-7 | | y/6-4=6 | | z/5-6=2/1/6 | | -15h-8.8h-20=20-19.8h | | 12g-3g--9g=-18g | | 0=5x^2+4x-18 | | 3x-9=68-4x | | r-7.4=-7.1 | | -1/7(7y+8) |